Problem-based learning vs traditional method in the development of competencies in students in the health area. A systematic review - Vélez Silva, Vicenta Nazaela; Palma Zambrano, Génesis Adriana; Borroto Cruz, Eugenio Radamés (Salud, Ciencia y Tecnología, 2024)
Introduction: Problem-based learning (PBL) is a student-centered pedagogical approach based on self-directed learning. It is increasingly used in medical education and there are contradictions about its superiority with respect to traditional learning methods.Objective: Compare PBL with the traditional method in the development of competencies in students in the health areaMethodology: Systematic reviews and meta-analyses published in specialized databases such as Pubmed, Cochrane, ERIC and Scielo were used. A search strategy based on Mesh terms and Boolean operators was used. Free access publications were selected, up to 10 years old, with a level of compliance with the PRISMA checklist >95%.Results: 446 eligible articles were identified, of which only 13 were selected, of which 10 were systematic reviews with meta-analyses. Students from various medical disciplines were included. No statistically significant differences were reported between both study methods in 3 articles (p>0.05); while, in 10 articles, it was concluded that the PBL method is superior to traditional learning methods (p<0.05). Although most authors agree that PBL is superior to traditional methods, they also conclude that it is necessary to provide more evidence in this regard.Conclusions: PBL appears to be superior to traditional learning methods in medical education; However, there is not enough evidence to support this approach. It is necessary to deepen the comparative study of both learning methods.